Comparative study of lipidic stability of soybean, sorghum, oat, bran and wheat germ flours with and without extrusion (INNOTEC, 2013)
Consumption of whole grain flour is determined by the loss of nutritional, functional and sensory quality during storage. This study evaluates the effect of the extrusion process in the lipid degradation of flour of various types of cereal (soybean, sorghum, oat bran and wheat germ). Free fatty acids, moisture, activity and the development of the “rancid-oxidized” descriptor were followed up by direct olfaction in flour samples with and without extrusion stored for 60 days in a polyethylene bag of 30 micron to (30-35) ºC. The acceptability of bread made with 36% incorporation of a combination of flours was also studied. Measurements of color, fat and urease activity at the beginning, middle and end of storage were conducted. Regression functions were fitted to the difference “without extrusion” and “extrusion” for measures of AGL, Aw, % H. The results showed that extrusion significantly decreased lipid degradation of sorghum flour, bran, soybean, oat, however, the extruded germ meal had an increased oxidative rancidity. Incorporating flours without extruded bread dough decreased significantly the acceptability and affect the bread texture and volume.
Keywords: Multigrain flour; degradation; rancidity; hydrolysis; oxidation